2019
DOI: 10.3389/fmed.2019.00218
|View full text |Cite
|
Sign up to set email alerts
|

Health and Well-Being in Late Life: Gender Differences Worldwide

Abstract: Maintaining health and quality of life and decreasing the number of years lived with disabilities in old age are among the main challenges of aging societies worldwide. This paper aims to present current worldwide health-related gender inequalities throughout life, and especially in late life, as well as gender gaps in social and personal resources which affect health, functioning and well-being. This paper also addresses the question of whether gender gaps at younger ages tend to narrow in late life, due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
98
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(128 citation statements)
references
References 100 publications
9
98
0
7
Order By: Relevance
“…This finding is consistent with a significant body of research on gender differences in wellbeing in late life, which has generally reported that women experience more deterioration in wellbeing and mental health outcomes than do men in older adulthood (Carmel & Bernstein, 2003;Luppa et al, 2012), and that this gap continues to widen throughout the course of late life (Diener, Eunkook, Lucas, & Smith, 1999). A study by Carmel (2019) found that women in late life tend to have generally lower scores on indicators of wellbeing and coping resources than do men, and that women present more symptoms of distress, loneliness, and disability than do men. Some reasons that may account for at least some of this gender disparity may be the fact that older women are more likely to take on stressful family caregiving roles compared to older men (Marks, Lambert, & Choi, 2002) and are more likely to be widowed than men (Pinquart & Sörensen, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…This finding is consistent with a significant body of research on gender differences in wellbeing in late life, which has generally reported that women experience more deterioration in wellbeing and mental health outcomes than do men in older adulthood (Carmel & Bernstein, 2003;Luppa et al, 2012), and that this gap continues to widen throughout the course of late life (Diener, Eunkook, Lucas, & Smith, 1999). A study by Carmel (2019) found that women in late life tend to have generally lower scores on indicators of wellbeing and coping resources than do men, and that women present more symptoms of distress, loneliness, and disability than do men. Some reasons that may account for at least some of this gender disparity may be the fact that older women are more likely to take on stressful family caregiving roles compared to older men (Marks, Lambert, & Choi, 2002) and are more likely to be widowed than men (Pinquart & Sörensen, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…Lastly, the findings uncover important gender variations in the social determinants of SWB that in part, are likely influenced by particular gender identities, roles and responsibilities that inform access to and control over resources over the life course [85]. In Uganda, patriarchal structures and deep-rooted attitudes regarding roles, responsibilities and identities of men and women mean women are responsible for maintaining and reproducing the household and community by managing a larger share of the domestic labor compared to men over their life course [36].…”
Section: Discussionmentioning
confidence: 97%
“…On the contrary, severity of anxiety symptoms was not differentiated based on gender. Therefore, it may be postulated that although older women were shown to report altogether more worry, as well as more severe depressive and anxiety symptoms compared with older men (94), the novel COVID-19 circumstances imposed similar levels of anxiety on both genders. This study also explored IU in older individuals, using a gender invariant scale (95).…”
Section: Discussionmentioning
confidence: 99%